Determinant factors of procrastination behavior at work: A case study in the university context - Sunarta, Sunarta; Muafi, Muafi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Procrastination, or delaying or postponing something frequently, is often found at workplace including university staff. Many factors in personal characteristics, task characteristics, and organizational work settings can cause procrastination. The existing empirical literature on procrastination focuses mainly on student procrastination, with little attention paid to the procrastination patterns of academic staff. Therefore, by using social exchange theory, this study aims to discuss the factors that influence procrastination behavior in academic staff. This research examines the influence of achievement motivation, job satisfaction, and psychological contract fulfillment on procrastination directly or through organizational commitment. The study was conducted through a case study approach. This research uses a quantitative approach with a survey research design of 126 staff at one of the state universities in Yogyakarta. The research instrument was developed from previous research. The data were analyzed using partial least square (PLS) based on structural equation modeling (SEM). The research results show that only achievement motivation and organizational commitment have a negative influence on procrastination. Organizational commitment mediates the influence of achievement motivation on procrastination. Job satisfaction and fulfillment of the psychological contract do not directly influence procrastination yet through organizational commitment. The results of this research provide implications for the role of human resource management in controlling procrastination at work. In the university context, achievement motivation and organizational commitment have a dominant influence in controlling procrastination behavior.